Do dental undergraduates think that Thiel‐embalmed cadavers are a more realistic model for teaching exodontia?. (20th December 2016) - Hanson, C.; Wilkinson, T.; Macluskey, M.
Abstract: Introduction: Teaching exodontia to novice undergraduates requires a realistic model. Thiel‐embalmed cadavers retain the flexibility of the soft tissues and could be used to teach exodontia. Objective: The objective was to determine whether Thiel‐embalmed cadavers were perceived to be a more realistic model by undergraduates in comparison with mannequins. Materials and Methods: Over a period of 4 years (2011‐2014), students were randomly assigned into two groups: those taught exodontia on mannequins only (NT) and those who also experienced cadaveric teaching (T). This was followed by an assessment. Results: There were 174 students in the T group and 108 in the NT group. Sixty‐five per cent of the T group and 69% of the NT group provided feedback. Ninety‐eight per cent (98%) felt that they had been advantaged by being included in the group compared with 95% in the NT who felt disadvantaged. The majority (98%) thought that using the cadavers was advantageous and gave a realistic feel for soft tissue management (89%) and that it was similar to managing a patient (81%). Self‐reported confidence in undertaking an extraction was not different between the two groups ( P =.078), and performance in the extraction assessment was not significantly different between the two groups over the 4 years ( P =.8). Conclusion: The Thiel‐embalmed cadavers were well received by the students who found it a more realistic model for exodontia than a mannequin, even though this did not impact on their performance in a following assessment. Future work on these cadavers may be expanded to include surgical procedures.